Corporate social responsibility and shareholder's value: An event study analysis - Leonardo Becchetti; Rocco Ciciretti; Iftekhar Hasan (Federal Reserve Bank of Atlanta, 2007)
Corporate social responsibility (CSR) is increasingly a core component of corporate strategy in the global economy. In recent years its importance has become even greater, primarily because of the financial scandals, investors' losses, and reputational damage to listed companies. While corporations are busy adopting and enhancing CSR practices, there is (beyond very few notable exceptions) no established empirical research on CSR's impact and relevance in the capital market. This paper investigates this issue by tracing the market reaction to corporate entry and exit from the Domini 400 Social Index, recognized as a CSR benchmark, between 1990 and 2004. The paper highlights two main findings: a significant upward trend in absolute value abnormal returns, irrespective of the type of event (for example, addition or deletion from the index), and a significant negative effect on abnormal returns after exit announcements from the Domini index. The latter effect persists even after controlling for concurring financial distress shocks and stock market seasonality.
Keywords: G14; D21; L21; 330; corporate social responsibility; event study; Corporate Social Responsibility; Finanzmarkt; Stakeholder; Event Study; USA